PENGARUH LA NINA DAN EL NINO TERHADAP PENYAKIT DEMAM BERDARAH DENGUE DAN MALARIA DI INDONESIA - Indriyati, Liestiana; Mahanani, Uli (EnviroScienteae, 2024)
The phenomena of El nino and La nina are closely related to rainfall and its impact on various fields. Rainfall is an element of weather and climate that greatly influences all aspects of life including health, especially mosquito vector-borne diseases in Indonesia such as Dengue  hemorrhagic fever (DHF), malaria, chikungunya, zika, and others. In this regard, an analytical study was carried out on the effect of El nino and La nina on DHF and malaria cases in Indonesia. This paper is the result of data analysis from the study "The Influence of El nino and La nina on Seasonal Variability in South Kalimantan" and the data of DHF and malaria cases obtained from the Data and Information Center of the Ministry of Health of Indonesia. Descriptive analysis was carried out on the trend of DHF and malaria cases fluctuation associated with El nino and La nina phenomena that occurred throughout the time period 2007-2017. El nino and La nina phenomena affect fluctuations in DHF and malaria cases related to increased and decreased of rainfall which affect the growth and development and also the activity patterns of mosquito as vectors of transmitting DHF and malaria. The increase of DHF cases in Indonesia was influenced by "strong" El nino and "moderate" La nina while the increase of malaria cases in Indonesia was more influenced by "strong" and "moderate" La nina events.